(untitled) (EAAE Annual Conference Proceedings, 2019)
The Zagreb EAAE 2019 Annual Conference provides a unique opportunity to reflect the theme of 100-years long teaching of technical disciplines to architecture students and to present a selection of their early works created from the 1919s to the 1926s in construction courses at the Royal Technical High School of Architecture. When founded in 1919, the Zagreb Faculty of Architecture was originally named the Royal Technical High School. Until 1926 in architecture department four generations of architects were educated and altogether forty architects received the Royal Technical High School diploma. The name of the school itself meant that the educational context of construction courses was a distinct feature of the school. The teaching of technical disciplines to architecture students has long been recognized as important and challenging. In building construction courses’ syllabus students gain technical knowledge in technical drawing, building construction systems, building materials, structures, elements and detailing of construction systems.